Curcumin induces mitochondrial dysfunction-associated oxidative DNA damage in ovarian cancer cells - Qi Bao; Zihan Wang; Tingting Yang; Xiao Su; Ying Chen; Lifen Liu; Qicheng Deng; Qingyang Liu; Changshun Shao; Weipei Zhu (PLoS ONE, 2025)
Resistance to chemotherapeutic agents is a critical challenge for the clinical management of ovarian cancer. While curcumin has been reported to possess anti-cancer properties, how it exerts its anti-neoplastic effect on ovarian cancer cells remains to be explored. We here characterized the fate of human ovarian cancer cell lines HO8910 and OVCAR3 treated with curcumin. Cell proliferation, cell death, mitochondrial function, oxidative damage and tumor formation in nude mice were examined. Significant inhibition of proliferation and induction of apoptosis were observed in ovarian cells treated with curcumin. The cancer cells exhibit cell cycle arrest at G2/M phase, mitochondrial accumulation, mitochondrial oxidative stress and high level of DNA damage after curcumin treatment. This effect of curcumin is independent of the BRCA mutation status. Curcumin-induced proliferation inhibition and apoptosis were effectively attenuated by the application of antioxidant N-acetylcysteine (NAC), suggesting that curcumin exerts its anti-cancer effect by inflicting oxidative stress. Curcumin applied at 200 mg/kg intraperitoneal infusion daily also inhibited the growth, oxidative damage, and mitochondrial accumulation of tumor xenografts in vivo. Together, the results indicate that curcumin can exert its anti-tumor effect via inducing mitochondrial dysfunction-associated oxidative DNA damage and can be potentially used in combination with other DNA repair-interfering therapeutics, such as PARP inhibitor, in the treatment of ovarian cancer.